A força plástica da cena: por uma pedagogia do excesso - Borges, Diego Landim (2025)
This research addresses the author’s experience as a professor in the Theater-Degree course at the Federal University of Ceará, based on two subjects taught: Directing Laboratory: from text to scene, and Visual studies of the scene, the latter marked by the presence of the blind student Anchieta de Carvalho. The area of activity brought the author closer to the materialities of the stage (light, scenography, costumes, etc.) as a principle for conducting the work. Based on his experience with Anchieta, the author proposes the recovery of the term plasticities in the face of “visualities” in the theatrical context, criticizing the centrality of the vision in contemporary times, on the one hand, and the symbolic forms of theatrical representation, on the other. Georges Bataille (2016; 2014) permeates and disturbs the entire research, which promotes unformed poetics of creation and thought. Thus, the sense of “tactility” and “eccentricity” also guides it. The first movement of the research investigates the themes he worked on in the classroom based on the notion of flesh-thinking and excess. To this end, the relationships between painting and theater based in Francis Bacon, Antonin Artaud’s theater, Buñuel’s cinema, and Manoel de Barros’ disruptive poetry, among others, provide theoretical and sensitive turning points. In the second movement, he focuses on the methodological procedures in the disciplines through notions such as “space,” “writing,” “vision,” and “scenography.” In an essayistic and kaleidoscopic writing, the author handles topics that obey the articulated logic of the organism — mouth, eye, skin, bone — that is exceeded by the sensitive contact of the flesh. He bases his notion of excess on Bataille and of flesh on Bacon (2007) and MerleauPonty (2014). Interviews, photos and reports are paired with the analyses of the “symptom” and the unformed in Georges Didi-Huberman (2015). Through research, the author attempts to counterpose the flesh to the digital injunctions that mark the contemporary era. Thus, the author proposes plasticity as a pedagogical practice of excess.